Back Cover: Complementary middle‐down and intact monoclonal antibody proteoform characterization by capillary zone electrophoresis – mass spectrometry. Issue 16 (21st August 2018) - Belov, Arseniy M.; Zang, Li; Sebastiano, Roberto; Santos, Marcia R.; Bush, David R.; Karger, Barry L.; Ivanov, Alexander R.
Abstract : DOI:10.1002/elps.201800067 The cover picture shows a set of electropherograms for middle‐down, intact, and native capillary zone electrophoresis‐mass spectrometry (CZE–MS) experiments (top panel) . The bottom panel shows, on the left, the results of the middle‐down CZE–MS experiment, involving the IdeS ‐digested, reduced mAb sample together with the experimental workflow. Major separated forms of the FC /2 fragment are highlighted. In the middle section, the separated predominant mAb proteoforms with different extents of glycosylation detected in the intact CZE‐MS experiment are presented. Finally, the major molecular species, including mAb dimers and partially disassembled mAb forms, detected in the native CZE‐MS experiment are shown as an ion density map in the section on the right .